Isótopos de carbono (¹³C) e a dinâmica do carbono orgânico do solo em sistemas cultivados no cerrado mineiro - Resende, Thalita Mendes (2015)
Agriculture and pasture dominate the landscapes that were originally covered by Cerrado vegetation in the Triangulo Mineiro (MG). The use of conversion causes a range of environmental changes, for instance, the imbalances of the carbon stocks, the nature of carbon sources and the reduction of carbon attached to a biomass accompanied by the modifications of the properties and the soil characteristics such as density, porosity and others. Being an essential pool to carbon storage, the soils can be a source or a sink of atmospheric CO2 that depending on the cultivation and the management system adopted. The micro-region of the Triangulo Mineiro (MG) in Uberlandia has extensive areas filled by pasture. However, the geological conditions of soil and the climate are important factors that may accelerate the soil degradation when pastures is not handled properly. The objectives of this research were to evaluate the alterations in soil organic matter (SOM), the variation in the stock of soil organic carbon (Mg/ha de C), the content and nature of carbon (%C e δ13C), the carbon replacement rate derived from the native vegetation C3 (in their stable and biodegradable pools) and the C4 crop in the ground and also to determine the turnover of SOM and the technical management efficiency to store carbon in areas covered with native Cerrado (CN - vegetation type Cerradão) and the cultivated pasture with 30 years of implementation (P30). It was studied a mixed and representative complex system in the region - an area that was initially converted to agricultural use and the last 15 years has been occupied with cultivated pasture (Agric+P15). It has been also done a meta-analysis from scientific literature data in order to evaluate the soil carbon storage alterations after changing of use including different areas in the Cerrado Mineiro. The results have shown that the conversion to cultivated systems had a decrease of total porosity (Pt) and an increase of soil density (Ds) when are compared with values determined for Cerradão soils. In soil under Agric+P15 there was an impoverishment of carbon content, especially, when compared to the surface area of native vegetation. Therefore, the soil covered with P30 showed values closer to those found in native vegetation in both surface and subsurface that was an evidence of a stability of the carbon content over time. There was a decrease of the storage of SOM on the superficial layers (0-15 cm) of the cultivated soil, however, in the depth (30-60 cm), the stock given in P30 is equivalent at the storage of the soil beneath Cerrado. In agric+P15 were determined lower inventories stock at all depths. The pasture management techniques was efficient in storing carbon, mainly if was taken the sandy soil formation (between 70 and 80% of sand). The results have shown that in Agric+P15 and in P30 there were an incorporation of C originated from vegetation C4. The average replacement of SOM derived from C4 plants (in 0-15 cm) was high, with 91,3% in Agric+P15 and 99,6% in P30. Finally, the carbon derivate of native vegetation had a low stable fraction (~2,2 t/ha de C) when is compared to the biodegradable fraction.